Sensory evaluation of fresh/frozen mackerel products: A review. Issue 4 (19th June 2021) - Huang, Yi‐Zhen; Liu, Yu; Jin, Zheng; Cheng, Qiaofen; Qian, Michael; Zhu, Bei‐Wei; Dong, Xiu‐Ping
Abstract: Mackerel has received considerable attention in the global food market as one of the most important pelagic commercial fish species. The quality of mackerel is influenced by species, season, fishing area, nutritional status, catching method, handling, and storage. Due to the mackerel's perishability, its quality is mainly measured by sensory procedures. Although considerable effort has been made to explore quick and reliable quality analysis, developing a practical and scientific sensory evaluation of mackerel has been an active ongoing study area to meet the quality evaluation demand of the industry. Different sensory evaluation methods have been used to assess the mackerel fish quality, including Palatability and Spoilage test, Torry scheme, EU scheme, Quality Index Method, Catch damage index and Processed fish damage index, Affective test, Discriminative test, and Descriptive test. Each method has its strength and weakness. Despite mackerel sensory evaluation protocols having undergone partial harmonization, specific sample process needs to be carefully followed to minimize the change during sample preparation. This review summarizes the sensory evaluation methods in mackerel research, the factors affecting sensory evaluation, and then updates the latest advances in mackerel sensory evaluation and offers guidance for presenting its application in the mackerel chain. Also, each technique's advantages and limitations are discussed. In our opinion, the future trends for sensory evaluation of mackerel should be consumer‐centric.